The role of endocannabinoid signaling in the cytoskeleton functionality in migrating neurons - Morozov, Yury M.; Rakic, Pasko (Medical Research Archives, 2025)
A fraction of neurons migrating through the developing brain are known to show nuclear envelope rupture and herniation of the chromatin in cytoplasm. We recently reported powerful streams of chromatin rupturing nuclear envelopes together with the plasma membranes in migrating cerebral neurons in mouse embryos. Such chromatin streams represent a novel form of cell pathology, which we named ‘piercing nuclear hernia’ (PNH). Simultaneous piercing of the nuclear and plasma membranes exposes nucleoplasm and cytoplasm to the intercellular space and may result in accidental cell death which, in contrast to the programed cell death mechanisms, are not detectable using biochemical or immunochemical markers for apoptosis, autophagy, or necrotic type of cell death. We also showed that the disfunction of the endocannabinoid system increases the probability of nuclear membrane rupture and chromatin herniation in developing brain. Indeed, about 40% of migrating neurons in cannabinoid type 1 receptor knock-out mouse embryos and wild type embryos exposed to two different agonists of the cannabinoid receptor show nuclear envelope ruptures or/and PNHs. This indicates that deviations from optimal functioning of the endocannabinoid system in under- or over-activity may trigger analogous mechanisms increasing the membrane’s vulnerability and chromatin herniation. The role of increased intranuclear pressure and cytoskeleton malfunction in the mechanism of nuclear envelope rupture is documented and commonly accepted. In accordance, our results provide evidence that optimal endocannabinoid signaling plays a role in cytoskeleton functionality in migrating neurons. In a fraction of neurons, catastrophic rupture of the nuclear and plasma membranes provokes ultrastructural pathology in the mitochondria and other organelles. At the same time, other neurons with PNH show generally normal ultrastructure that may indicate a mechanism of neuronal cell body repair. Further studies of neuronal cell body recovery may identify yet unknown molecular mechanisms and become instrumental for increasing regenerative capacity of neurons during neurodegenerative diseases, after traumatic brain injury and ischemic conditions. On the other hand, the demonstrated novel pathology of PNH in migrating cells and the procedure of its upregulation may be useful for inducing breaks of the plasma membrane and death of metastatic tumor cells.